ANALISIS KAJIAN TEORITIS PERBEDAAN, PERSAMAAN DAN INKLUSI DALAM PELAYANAN PENDIDIKAN DASAR BAGI ANAK BERKEBUTUHAN KHUSUS (ABK) - Siti Hajar; MG.Sri Roch Mulyani (JURNAL MITRA SWARA GANESHA, 2017)
ABSTRACK Inclusion as an education service for children with spesial need thoroughly. The purpose of education inclusion to develop potential in limitations of the person. Study of the theory about the difference or diversity, equity and inclusion or equations must be understood before it hosts the educational inclusion. The implementation of inclusion ranging from basic education will contribution positively to the planting base of life for the person. Â Key words : Diversity, Equality and Inclusion